Evaluation of the anatase/rutile phase composition influence on the photocatalytic performances of mesoporous TiO2 powders. (9th November 2015) - Masolo, Elisabetta; Senes, Nina; Pellicer, Eva; Baró, Maria Dolors; Enzo, Stefano; Pilo, Maria Itria; Mulas, Gabriele; Garroni, Sebastiano
Abstract: We investigated the influence of the microstructure, texture and the relative amount of anatase and rutile phases on the photoelectrocatalytic H2 evolution over mesoporous TiO2 (m-TiO2 ). This study was carried out by means of ex-situ powder X-ray diffraction (XRPD), N2 physisorption, transmission electron microscopy (TEM), and photoelectrolysis measurements. The synthesis of nanocrystalline TiO2 powders with different anatase/rutile weight ratios was successfully approached by evaporation-induced self assembly (EISA) method simply varying the volume amount of TiCl4 and Ti(OBu)4 (acid–base pair) as metal precursors. In particular, m-TiO2 with anatase/rutile weight ratios similar to commercial TiO2 (P25) was obtained. The microstructure, texture and photocatalytic properties toward hydrogen evolution reaction (HER) of the as-synthesized TiO2 were compared with commercial P25. Interestingly, the m-TiO2 with a high surface area of 196 m 2 /g, uniform pore size and 87/13 anatase/rutile weight ratio, showed a significant increase in the photoactivity with respect to the powders richer in either anatase or rutile phases. Furthermore, it was claimed that the crystallinity and specific surface area play a key role on the photocatalytic activity of the synthesized m-TiO2 samples. Graphical abstract: Highlights: Synthesis of mesoporous TiO2 powders with tunable anatase/rutile phase composition. Effect of structure and morphology on photocatalytic H2 production. High surface area related to higher photoactivity. Importance of the superior crystallinity of P25 for better performances.